Melindungi Akidah Anak dari Bahaya Dunia Modern Melalui Pendidikan Keluarga - Irwan Sulistyanto; Yuslia Styawati (Universitas Islam Tribakti Lirboyo Kediri, 2022)
The Muslim personality is formed from an early age, parents as a Muslim must have a quality belief in monotheism. But it would be nice if parents also understand monotheism materials, so that parents can equip their children with knowledge that is supported by the example of monotheism so that the personality of a true Muslim is formed. The family is the first environment for the formation of the unity of the child. In writing this scientific paper, the author uses the type of research